Desain dan Implementasi Bidirectional DC-DC Converter Untuk Penerangan Darurat - Nancy Rahayu; Irianto Irianto; Eka Prasetyono (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2020)
The lighting system is one of the biggest uses of electrical energy. Currently, lighting systems, especially emergency lighting, are urgently needed to deal with sudden blackouts at night. The emergency lighting gets a source of electrical energy from the battery and the battery gets a source of electrical energy from PLN. To regulate the source of electrical energy, a DC-DC converter with a bidirectional method is used. The bidirectional converter is a converter that has 2 functions, namely buck mode and boost mode which works when the main source of PLN goes out, automatically the lighting system will be supplied by the battery as a backup source. The buck mode in the charging process is used to store electrical energy into a battery with a battery capacity of 12V 30Ah. While the boost mode in the discharging process is used to distribute electrical energy from the battery to the load with a lamp load of 10W. The charging and discharging processes are controlled using proportional integral control analytic methods. The charging process in buck mode with a Kp value of 8.62 and Ki of 17240, the output voltage value is 13.99V. While the discharging process in boost mode with a Kp value of 2.44 and Ki of 344.63, the output voltage value is 23.99V.